2022
DOI: 10.1371/journal.pone.0277831
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Directional Axial Transmission measurements applied in a clinical environment

Abstract: Accurate measurement of cortical bone parameters may improve fracture risk assessment and help clinicians on the best treatment strategy. Patients at risk of fracture are currently detected using the current X-Ray gold standard DXA (Dual XRay Absorptiometry). Different alternatives, such as 3D X-Rays, Magnetic Resonance Imaging or Quantitative Ultrasound (QUS) devices, have been proposed, the latter having advantages of being portable and sensitive to mechanical and geometrical properties. The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…The technique also allows waveguide characteristics of the bone, such as cortical thickness and/or porosity, to be estimated from dispersion curves by fitting a theoretical waveguide model [265][266][267][268]. Although preliminary applications in vivo show promise [269,270], soft tissue properties, multimode overlap, and the conversion of guided waves still present a significant challenge for the routine in vivo use of ultrasonic guided waves for the quantification of cortical bone fracture [271,272]. Moreover, further prospective research studies are needed to demonstrate the clinical potential of axial-transmission techniques for quantifying fracture characteristics in cortical bone and the subsequent healing stages.…”
Section: Measurement Of Bone Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique also allows waveguide characteristics of the bone, such as cortical thickness and/or porosity, to be estimated from dispersion curves by fitting a theoretical waveguide model [265][266][267][268]. Although preliminary applications in vivo show promise [269,270], soft tissue properties, multimode overlap, and the conversion of guided waves still present a significant challenge for the routine in vivo use of ultrasonic guided waves for the quantification of cortical bone fracture [271,272]. Moreover, further prospective research studies are needed to demonstrate the clinical potential of axial-transmission techniques for quantifying fracture characteristics in cortical bone and the subsequent healing stages.…”
Section: Measurement Of Bone Propertiesmentioning
confidence: 99%
“…Current applications have already demonstrated that UCT has the capacity to provide images from various reconstructed acoustic parameters, including the propagation velocity of axial ultrasound waves [367], density, and attenuation [358]. Sequential scanning approaches, such as those used in synthetic transmit aperture (STA) imaging [368], represent a natural extension of current bi-directional transmission approaches [270] and may be a useful adjuvant to aid multiparameter imaging. Simultaneous developments in wearable ultrasonic arrays are likely to yield viable low-cost methods for extended, serial, and multi-parameter transmission measurements of musculoskeletal tissues that can be acquired at rest during activities of daily living and in settings outside the hospital or the laboratory [369].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Two particular regions of the spectrum are visually followed: the upper part, associated with the slowest wave or A 0 mode, and the lower part, associated with the highest phase velocities and the modes traveling within the two cortical bone interfaces (J. Minonzio et al 2020).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Osteoporosis is a systemic disease, in which the bone composition changes over time (J. Minonzio et al 2020;J.-G. Minonzio et al 2019).…”
Section: Future Directionsmentioning
confidence: 99%